(untitled) (Bangladesh Journal of Botany, 2018)
Strong and negative correlation was observed between the yield of marketable cabbage heads and populations of/plant infestations by cabbage aphid (Brevicoryne brassicae L.) 14 days after first and second spray. Weak correlation existed between yield of marketable cabbage heads and aphid populations/plant infestations at pre-treatment. Therefore, insecticide sprays should be done to control late aphid infestations and avoided against early aphid infestations.